2020
DOI: 10.1186/s12866-020-01774-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bacterial communities in soil samples with and without tomato bacterial wilt caused by Ralstonia solanacearum species complex

Abstract: Background: Ralstonia solanacearum is one of the most notorious soil-borne phytopathogens. It causes a severe wilt disease with deadly effects on many economically important crops. The microbita of disease-suppressive soils are thought that they can contribute to the disease resistance of crop plants, thus, evaluation of the microbial community and their interaction characteristics between suppressive soil (SS) and conducive soil (CS) will help to understand resistance mechanism. To do this, the bacterial comm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…Our study revealed that disease altered the network features of the soil and root microbiomes. In particular, the co-occurrence networks of the suppressive soil and healthy roots were more complex, with a higher number of edges, higher average degree, and clustering coefficient compared with the networks of the conducive soil and infected roots ( Figure 4 ); this is consistent with previous studies ( Qi et al, 2019 ; Wei et al, 2019 ; Zhang et al, 2020 ). It was indicated that complex networks are more robust to external biotic and abiotic stresses than simple networks ( Santolini and Barabási, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study revealed that disease altered the network features of the soil and root microbiomes. In particular, the co-occurrence networks of the suppressive soil and healthy roots were more complex, with a higher number of edges, higher average degree, and clustering coefficient compared with the networks of the conducive soil and infected roots ( Figure 4 ); this is consistent with previous studies ( Qi et al, 2019 ; Wei et al, 2019 ; Zhang et al, 2020 ). It was indicated that complex networks are more robust to external biotic and abiotic stresses than simple networks ( Santolini and Barabási, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…The soil with low disease incidence even in the coexistence of susceptible plants and pathogens was defined as disease-suppressive soil. The mechanisms behind soil-mediated suppression of diseases, such as bacterial wilt disease in tobacco ( Qi et al, 2019 ; Zhang et al, 2020 ), Fusarium wilt in vanilla ( Xiong et al, 2017 ), Rhizoctonia solani in sugar beet ( Mendes et al, 2011 ), and black root rot in tobacco ( Kyselkova et al, 2009 ), have been extensively investigated. The soil microbiome has been deciphered in detail, and it has been found that the soil compositions between suppressive and conducive soils are distinct, although they share similar geographical and climatic conditions, as well as the same agronomic management.…”
Section: Introductionmentioning
confidence: 99%
“…We found different genotypes of connectors and module hubs and differences between periods. In the seedling stage, the connectors found in N were all related to functions such as cellulose degradation and plant growth and development (Koeck et al 2016;Zhang et al 2020). The connector found in QZ was related to bacterial exopolysaccharides (EPSs), which can provide the host plant with antioxidants and protection from corrosive pathogens (Supplementary Table S4) (Bouchotroch et al 2000;Chi et al 2019).…”
Section: )mentioning
confidence: 99%
“…The pathogen R. solanacearum is a complex species with obvious physiological differentiation and genetic diversity and a very wide host range. R. solanacearum can infect more than 200 species in 54 families of plants (Prior et al, 2016), including tomato, tobacco, potato, banana, pepper, etc., thereby posing a serious threat to food security (Zhang et al, 2020). TBW is a vascular disease that often breaks out under the conditions of high temperatures and high humidity (Choi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%